2022
DOI: 10.3390/agronomy12061383
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plant-Growth Promoting Rhizobacteria and Mycorrhizal Fungi Consortium as a Strategy to Improve Chickpea (Cicer arietinum L.) Productivity under Different Irrigation Regimes

Abstract: Climate change prediction indicates an increased likelihood of precipitation variability and droughts in the Mediterranean region. Previous studies demonstrated that microbial symbionts combined with supplementary irrigation could mitigate climate change effects and boost chickpea production in low-fertility soils. The aim of the study was to assess the effects of inoculation with a consortium of plant growth-promoting rhizobacteria (PGPR) (Pseudomonas sp., Burkholderia sp. and Mesorhizobium sp.) and arbuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…A positive correlation between high early vigor and plant yield was already established [ 36 , 37 ]. According to earlier studies, irrigation application had beneficial impacts on phosphate solubilization, microorganism activity, crop growth, and development in chickpea cultivars [ 38 , 39 ]. Another report elaborated that irrigation supplementation significantly enhanced the numbers of nodules and seed yield in chickpea [ 22 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between high early vigor and plant yield was already established [ 36 , 37 ]. According to earlier studies, irrigation application had beneficial impacts on phosphate solubilization, microorganism activity, crop growth, and development in chickpea cultivars [ 38 , 39 ]. Another report elaborated that irrigation supplementation significantly enhanced the numbers of nodules and seed yield in chickpea [ 22 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the spatial and/or sequential association of different genera of rhizobacteria and AMF can provide customized benefits to roots within their microenvironment. For example, it has been revealed that certain rhizobacterial strains belonging to the Proteobacteria class, such as Pseudomonas sp., Burkholderia sp., and Mesorhizobiu m sp., predominantly showed close association with AMF in the chickpea rhizosphere (Laranjeira et al., 2022).…”
Section: Chickpea Rhizospherementioning
confidence: 99%
“…These symbionts have significant potential to not only improve the productivity but also enhance the quality of Chickpea under deficit conditions. This association increased protein content by 3.9%–19.1% compared with non‐infectious plants of chickpea under water deficit conditions (Laranjeira et al., 2022). Furthermore, under moderate water deficit conditions, the symbiotic associations with Mesorhizobium mediterraneum, Rhizophagus irregularis , and their combination ( Mesorhizobium mediterraneum + Rhizophagus irregularis ) have demonstrated the potential to enhance the chickpea growth and improve crude protein content by 13%, 17%, and 22%, respectively (Oliveira et al., 2017).…”
Section: Facilitating Chickpea Growth and Productivity Through Symbio...mentioning
confidence: 99%
See 2 more Smart Citations